Implante primário de lente-intraocular para o tratamento da catarata congênita e do desenvolvimento - Silva, Virgílio Figueiredo [UNESP] (2014)
Purpose: Evaluated the reproducibility, intraoperative and postoperative complications and refractive results by technique of primary IOL implantation followed by posterior capsulotomy and anterior vitrectomy via pars plana / plicata for treatment of congenital cataracts and development. Patients and methods: Children with congenital cataract and development, unilateral or bilateral with surgical indication aged zero to 12 years. Eyes less than 10 mm horizontal corneal diameter or other changes were excluded. Results: 50 eyes of 35 children and 18 males (51.42 %) and 17 female (48.58 %) . The age ranged from 2 months to 12 years. 20 eyes were of children under 1 year of age. 19 cases (76 %) had bilateral cataracts and 12 unilateral cases (24 %). No intraoperative complications were observed. Regarding postoperative complications, observed opacity of the visual axis and need to surgery in 6 eyes ( 12 % ) , 4 eyes operated under 1 year of age ( 20 % of children in this age group ) and 2 eyes older than 1 year of age ( 6.67 % of children in this age group ). Conclusion: The technique was shown to be reproducible, with mild postoperative complications and appropriate refractive results